KLITIKALISASI VERBA BAHASA LAMAHOLOT DIALEK RITAEBANG - Emmy Renoat (Jurnal Lazuardi, 2022)
This study contains an analysis of the cliticalization of verbs in the Ritaebang dialect of Lamaholot. In BLDR there are proclitics and enclitics attached to verbs. This type of research is descriptive qualitative research. The research method used is the method of observation and interviews, then the data obtained were analyzed using the agih method and the padan method. In BLDR, proclitics attached to action verbs can replace pronouns completely. when proclitic is attached to an action verb in a clause, the subject is not required to be present, but the clause is present in the BLDR user community. In addition, the proclitic attached to action verbs can also be an answer to the question 'what did A do?'. The same thing happens with enclitics which indirectly affect the object. In addition, the presence of enclitics attached to action verbs can also be an answer to the question 'what did A do?'. Thus, it can be said that both proclitic and enclitic in BLDR are only attached to action verbs and have the same effect and function in a BLDR clause.